Assessing Australian women’s knowledge and knowledge preferences about long-term health after hypertensive disorders of pregnancy: a survey study - Caroline S E Homer; Mark Brown; Amanda Henry; Heike Roth; Grace LeMarquand; Lynne M Roberts; LIsa Hanley (BMJ Open)
Objectives To (1) assess women’s current knowledge regarding long-term cardiovascular health after hypertensive disorders of pregnancy (2) elicit women’s preferred educational content and format regarding health after hypertensive disorders of pregnancy.Design and setting A custom-created online survey exploring Australian women’s knowledge about long-term health after hypertensive disorders of pregnancy, distributed through consumer groups and social media.Participants 266 women with (n=174) or without (n=92) a history of hypertensive disorders of pregnancy.Primary and secondary outcome measures (1) Proportion of women identifying long-term health risks after hypertensive disorder of pregnancy using a 10-point risk knowledge score with 0–4 ‘low’, 4.1–7.0 ‘moderate’ and 7.1–10 ‘high’. (2) Exploration of preferred content, format and distribution of educational material post hypertensive disorder of pregnancy.Results Knowledge scores about health after hypertensive disorder of pregnancy were moderate in groups with and without a history of the disorder. Knowledge was highest regarding risk of recurrent hypertensive disorders in a subsequent pregnancy, ‘moderate’ for chronic hypertension and heart attack, ‘moderate’ and ‘low’ regarding risk of heart disease and ‘low’ for diabetes and renal disease. Only 36% of all participants were aware that risks start within 10 years after the affected pregnancy. The majority of respondents with a history of hypertensive disorder of pregnancy (76%) preferred receiving information about long-term health 0–6 months post partum from a healthcare provider (80%), key organisations (60%), social media (47%) and brochures/flyers (43%).Conclusions Women’s knowledge regarding health risks after hypertensive disorder of pregnancy was ‘moderate’, although with important disease-specific gaps such as increased risk of diabetes. Most women wanted to be informed about their long-term health from a healthcare provider.